An Assessment of Cilacap Coast's Total Carbonate Sediment Content - Mukti Trenggono; Roy Andreas; Amron Amron; Rizqi Rizaldi Hidayat; Hendrayana Hendrayana; Rr Diah Febri Astuti; Cristiana Manullang (Universitas Diponegoro, 2021)
Sediments are particles derived from the dismantling of rocks from the land and pieces of shell and remains of marine organisms that contain organic matter, included carbonate sediment. The total carbonate sediment content was influenced by many factors, such as sediment grain type. This study aimed to determine the carbonate content in sediments and to determine their relationship to the sediment grain characteristic on the Cilacap coast. The sediment's carbonate content used the titration method, while the sediment grain test used a dry filter. Statistical analysis was used to determine the sediment grain characteristic (mean, sorting, skewness, and kurtosis). The results showed that sediments' total carbonate content had a range of 1.93% - 6.23%, with an average of 4.21%. Sediments are dominated by fine sand with very well sorted, very platykurtic, and very fine skewed characteristics. The relationship between sediment grain characteristics and total sediment carbonate content showed a good correlation due to the sorting factor. Other parameters such as mean size and skewness have been shown a low correlation, whereas kurtosis has a shallow relationship with carbonate content.